A Diaspora Moment: Writing Global History Through Palestinian-West German Ties. Issue 3 (29th November 2022) - Prestel, Joseph Ben
Abstract: While the West German Left had been a staunch supporter of Israel until 1967, ties between Palestinians and the country's radical Left flourished after the Six-Day War. At the same time, a Palestine solidarity movement emerged in the Federal Republic. Since the late 1970s, these ties weakened again, and critical questions about Palestinian politics multiplied. How can historians explain these ebbs and flows of pro-Palestinian activism? The untapped Palestinian archive of solidarity movements offers a new perspective on a story of transnational radicalism, situating developments that have long been seen as internal affairs in national histories in a global context. A combined study of Palestinian and German documents reveals the central role that the Palestinian diaspora played in the spread of solidarity movements in Western Europe. The displaced nature of Palestinian politics ultimately illustrates the limitations of national histories and categories like domestic and foreign, internal and external. Looking at Palestinian-West German ties through a Palestinian lens sheds light on a diaspora moment that stretched from the 1950s into the 1980s, when actors without a state shaped leftist politics that bridged Western Europe and the Middle East.